Effects of Chilling and Anoxia on the Irradiation Dose-Response in Adult Aedes Mosquitoes - Yamada, H.; Maiga, H.; Kraupa, C.; Mamai, W.; Bimbilé Somda, N. S.; Abrahim, A.; Wallner, T.; Bouyer, J. (Frontiers in Bioengineering and Biotechnology, 2022)
The success of the sterile insect technique (SIT) relies on the achievement of high levels of sterility and mating success of the factory-reared sterile males and thus their biological quality, which can be enhanced by the reduction of stress factors encountered during rearing, handling, and irradiation procedures. The achievement of consistent sterility levels requires reliable and standard irradiation protocols. Additionally, mosquito adults require immobilization prior to, and during irradiation to increase processing efficiency and to avoid physical damage caused by movement in restricted space. Common methods for immobilization include chilling and anesthetics such as nitrogen. Here we assessed the effects of chilling and exposure to nitrogen on the irradiation dose-response of Aedes mosquitoes, and their downstream effects on select male quality parameters including longevity and flight ability. We found that chilling induces damage in the insects when treated as adults, reducing longevity and flight ability, but partial or full recovery is possible if chilling duration and temperature are carefully controlled. Irradiation in nitrogen shows high radioprotective effects during irradiation, resulting in reduced induction of sterility. Overall, longevity of males can be improved by irradiating in anoxia, however the exposure to nitrogen itself comes with negative impacts on flight ability. The results reported here will assist in the standardization and optimization of irradiation protocols for the SIT to control mosquito populations of medical relevance.